2023
DOI: 10.1101/2023.04.29.538828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell atlas of the aging murine ovary

Abstract: Ovarian aging leads to diminished fertility, dysregulated endocrine signaling, and increased chronic disease burden. These effects begin to emerge long before follicular exhaustion. Around 35 years old, women experience a sharp decline in fertility, corresponding to declines in oocyte quality. However, the field lacks a cellular map of the transcriptomic changes in the aging ovary to identify drivers of ovarian decline. To fill this gap, we performed single-cell RNA sequencing on ovarian tissue from young (3-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 121 publications
0
1
0
Order By: Relevance
“…Excessive amount of ECM, indicative of tissue brosis, is responsible for impaired ovarian function 32 . Increased in ammation and brosis occur before the exhaustion of follicles and probably lead to ovarian insu ciency 33 . Mast cells are mostly best known for their role in in ammation, and they are mainly located in ovarian stromal tissues 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive amount of ECM, indicative of tissue brosis, is responsible for impaired ovarian function 32 . Increased in ammation and brosis occur before the exhaustion of follicles and probably lead to ovarian insu ciency 33 . Mast cells are mostly best known for their role in in ammation, and they are mainly located in ovarian stromal tissues 34 .…”
Section: Discussionmentioning
confidence: 99%
“…reported the role of progesterone receptor in ovulation after the LH surge using an scRNA‐seq approach. 8 Although there have been other reports of single‐cell RNA sequencing in mouse ovaries, 9 , 10 , 11 , 12 the changes in the interactions between MGCs and CGCs during ovulation remain unclear. In this study, we performed in silico analysis of the reported scRNA‐seq data of mouse ovary to investigate the interactions between MGCs and CGCs during ovulation after the LH surge.…”
Section: Introductionmentioning
confidence: 99%